EFL TEACHERS’ STRATEGY IN TEACHING ENGLISH NARRATIVE WRITING DURING COVID-19 OUTBREAK - Jihan; Royana; Jumiyasrini; Sayit Abdul Karim; Nichella Ayu Clarita (UIBU, 2023)
The COVID-19 outbreak throughout the world forced the government of Indonesia to shift academic programs into online mode. The objectives of this study are to describe the teachers' strategies for teaching narrative writing during the COVID-19 outbreak and to find out the teachers' reasons to choose the strategies. Therefore, a qualitative research design was applied and the data was gathered through semi-structured interviews and online observation. Two exemplary teachers were involved as the respondents in the present study. Data coding was conducted to analyze the data gained from those research instruments. The findings revealed that the first respondent (JY) used cooperative learning, group discussion, and translation as her strategies in teaching English narrative writing text. Meanwhile, the second respondent (RN) used guided questions, cooperative learning, and translation as her strategies for teaching English narrative text during the pandemic. The findings showed that the first respondent (JY) utilized those strategies to increase students' participation, enhance students' vocabulary mastery, and developed student writing ability. Meanwhile, the second respondent (RN) utilized the aforementioned strategies to enrich students' vocabulary mastery, and improve students sentence structure.